Website-Based Student Savings Application - Jojo Adi Kusumah; Siti Sufaidah (LPPM Universitas KH. A. Wahab Hasbullah, 2025)
Student savings is one of the flagship programs at the Al-Husna Education Foundation, which aims to train students in managing finances from an early age. Through this program, students are taught to set aside some of their pocket money to meet school needs such as uniforms, tuition fees, and other activities. This program also plays a role in shaping the character of discipline, frugality, and responsibility. However, the previous savings management system was still manual, namely by recording transactions in savings books and cash books. This method is prone to cause recording errors, data loss, and a lack of information transparency for students' parents. In addition, manual recording becomes less efficient as the number of transactions increases. To address these problems, a website-based student savings management system has been developed to replace manual processes with automated systems. The system is built using the CodeIgniter 4 framework, the PHP programming language, and the MySQL database. The results of the study show that this system is able to make it easier to record transactions, present reports automatically, and provide fast, accurate, and transparent access to information for schools and parents of students.